Age-related degeneration of lumbar muscle morphology in healthy younger versus older men. (4th December 2020) - Dallaway, Alexander; Hattersley, John; Diokno, Michael; Tallis, Jason; Renshaw, Derek; Wilson, Adrian; Wayte, Sarah; Weedall, Andrew; Duncan, Michael
Abstract: Aim: The aim of this study was to evaluate age-related changes in lumbar paravertebral muscle (LPM) morphology in healthy younger and older adult men. Methods: T2-weighted axial MRI of the lumbar spine were obtained for 12 healthy older (67.3 ± 6.0 years) and younger (24.7 ± 3.1 years) men. Normalised muscle volume (NMV) and muscle fat infiltrate (MFI) were determined bilaterally for the psoas (PS), quadratus lumborum (QL), erector spinae (ES) and multifidus (MF). MANOVA was used to compare NMV and MFI between age groups. Follow-up ANOVA compared NMV and MFI for each muscle between age groups, with physical activity (PA) as a covariate. Stepwise regression was used to explore the association between muscle morphology. Results: NMV of the ES and QL were significantly lower in the older group (OG) ( p  = 0.040 and p  < 0.001, respectively). MFI across all muscles was significantly greater in the OG ( p  < 0.001). PA did not moderate the relationship between aging and muscle degeneration. Non-dominant handgrip strength was associated with NMV ( p  = 0.003). Conclusions: Age-related atrophy is muscle specific in the lumbar spine; changes in lumbar musculature is independent of PA, handgrip strength may reflect morphological changes in the postural muscles with age. This study supports establishing effective targeted exercise interventions in the lumbar musculature.